PENGEMBANGAN E-MODUL BERBASIS LITERASI SAINS MATERI ORGAN GERAK HEWAN DAN MANUSIA KELAS V SD - atmaji, rizan dwi; Maryani, Ika (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2019)
This type of research is development research with the ADDIE model. This research begins with analysis, design, development, implementation, and evaluation. The subjects in this study were media expert validators, material experts, learning experts, students, and teachers. The results of the development in the form of science-based e-modules are in the form of evaluations from expert validators and trials of students and teachers. The assessment of media experts received a score of 92.85 with the category "Very Worthy. Material experts received a rating of 92.85 in the "Very Worthy" category. The results of the assessment of learning experts get a value of 73.21 with the category "Eligible". the assessment of small-scale trials conducted by students gets a score of 95 with the category "Very Worthy" and the assessment of the teacher gets a score of 95 with the category "Very Worthy". The large-scale trials conducted by students got a score of 96.6 with the category "Very Worthy" and the assessment of the teacher received a score of 97.08 with the category "Very Worthy". Based on the results of the research obtained, science-based e-modules are very feasible to be used in the learning process at school.